2007
DOI: 10.1074/jbc.m604740200
|View full text |Cite
|
Sign up to set email alerts
|

Flippase Activity Detected with Unlabeled Lipids by Shape Changes of Giant Unilamellar Vesicles

Abstract: Transbilayer movement of phospholipids in biological membranes is mediated by energy-dependent and energy-independent flippases. Available methods for detection of flippase mediated transversal flip-flop are essentially based on spin-labeled or fluorescent lipid analogues. Here we demonstrate that shape change of giant unilamellar vesicles (GUVs) can be used as a new tool to study the occurrence and time scale of flippase-mediated transbilayer movement of unlabeled phospholipids. Insertion of lipids into the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 34 publications
3
58
0
Order By: Relevance
“…Likewise, protein pools with higher specific flippase activities were obtained in this study by fractionation; conversely, other fractions replete with membrane proteins were inactive. In addition, a recent study clearly demonstrated that the presence of membrane proteins in giant unilamellar vesicles per se is not sufficient to facilitate the flip-flop of phospholipids (31). These results reinforce the conclusion that specific proteins are required to facilitate phospholipid flip-flop; the data presented in this paper indicate that the identification of these proteins is feasible.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Likewise, protein pools with higher specific flippase activities were obtained in this study by fractionation; conversely, other fractions replete with membrane proteins were inactive. In addition, a recent study clearly demonstrated that the presence of membrane proteins in giant unilamellar vesicles per se is not sufficient to facilitate the flip-flop of phospholipids (31). These results reinforce the conclusion that specific proteins are required to facilitate phospholipid flip-flop; the data presented in this paper indicate that the identification of these proteins is feasible.…”
Section: Discussionsupporting
confidence: 77%
“…Our experiments also allowed us to estimate that the flippase protein represents ϳ2% (wt/wt) of membrane proteins in the TE. Using ER membrane proteincontaining proteoliposomes such as those described here, we recently succeeded in reconstituting flippase activity in giant unilamellar vesicles (31), allowing us to study the time scale of flippase-mediated transbilayer movement of unlabeled phos- FIG. 6.…”
Section: Discussionmentioning
confidence: 99%
“…In model membranes of bilayer-forming lipids, the rate of spontaneous polar lipid movement between bilayer leaflets is slow (hours to days for PtdCho lipids 37,38 ) and is governed by the size, charge and polarity of the head-group. The half life (t 1/2 ) for translocation is days for complex GSLs but seconds for Cer 39 , DAG 40,41 and sterols 42 .…”
Section: Lipid Dynamic Transmembrane Distributionmentioning
confidence: 99%
“…In lipid vesicles, this effect is seen as membrane budding. The budding can be induced by temperature or addition of lipids to the outer monolayer (i.e., by factors changing the monolayers area balance), in this case because of relative expansion of the outer monolayer (Dobereiner et al 1997;Papadopulos et al 2007). To compensate, the vesicle is transformed into a chain of smaller vesicles to match the new area disparity.…”
Section: Closed Membranes and Shape Diagramsmentioning
confidence: 99%
“…The enzyme adsorption causes changes in the area of the outer monolayer (Papadopulos et al 2007). The reaction products, such as ceramides, tend to aggregate forming rigid membrane domains (Holopainen et al 2000).…”
Section: Tuning Of Membrane Shapementioning
confidence: 99%